Enabling in situ protein analysis for pharmaceutical applications using 3D OrbiSIMS - Kotowska, Anna (2022)
In situ characterisation of proteins at surfaces is of interest to biological, biotechnological and pharmaceutical fields, specifically areas of research such as tissue imaging, biomaterials discovery, biosensor development and tissue engineering. Label-free protein characterization at surfaces is commonly achieved by matrix assisted laser desorption ionisation (MALDI) and requires digestion and/or matrix deposition prior to mass spectrometry, limiting the spatial resolution in two and three dimensions. This work presents the use of secondary ion mass spectrometry, 3D OrbiSIMS, to achieve the first matrix-, digestion- and label-free assignment of proteins in solid three-dimensional samples.